Cernuda in Current Spanish Poetry - Salvador J. Fajardo (Studies in 20th & 21st Century Literature, 2012)
The poet Luis Cernuda (Spain, 1902-Mexico, 1963) has left his mark on much of the poetry written in Spain since the sixties. First rediscovered in the Peninsula in the late fifties and early sixties by, among others, Francisco Brines, José Angel Valente, and Jaime Gil de Biedma, his influence became pervasive both through the work of these poets, and, through the reading of Cernuda’s poetry itself, available since 1975 in Harris and Maristany edition. Referring in particular to Biedma, whose impact on younger poets has been significant, this paper examines the presence of Cernuda in certain approaches to language and reality in the poetry of several “poetas de la experiencia” ‘poets of experience,’ such as Jesús García Montero, Felipe Benítez Reyes, and Álvaro García. Centering mainly on the simplification of language and the search for a non-rhetorical rhythm, developing in Cernuda from Invocaciones ‘Invocations,’ to Desolación de la Quimera ‘The Disconsolate Chimera,’ this article examines the same traits in Biedma. Thereafter it traces their incorporation in the poetry of García Montero, Benítez Reyes, and García. These readings offer an occasion to reflect on some of the strengths of the “poesía de la experiencia” that underlie its apparent straightforwardness and simplicity.
Keywords: poesía de la experiencia; poetas de la experiencia; poets of experience; Luis Cernuda; Spain; Spanish poetry; language; reality